BOD characteristics and their impact on the link between ESG disclosure and integrated reporting disclosure quality: a study of Egyptian non-financial firms - Zakia Abdelmoneim; Mohamed Samy El-Deeb (Future Business Journal, 2024)
Abstract This study examines the impact of environmental, social, and governance (ESG) disclosure on integrated reporting disclosure quality (IRDQ) and the moderating role of board of directors (BOD) characteristics. Prior research on ESG disclosure and IRDQ has been limited, especially in emerging economies like Egypt. Furthermore, the influence of BOD attributes has been underexplored. This study aims to address these gaps. A sample of 34 Egyptian non-financial companies under ESG disclosure mandates from 2015 to 2021 is analyzed using regression analysis. The results show a significant positive association between ESG disclosure and IRDQ. Furthermore, BOD gender diversity and size are found to positively moderate the ESG–IRDQ relationship. These findings highlight that appointing more women on boards and increasing board size can improve IRDQ when firms engage in ESG disclosure. However, the small sample size of ESG-mandated companies and inherent limitations in constructing disclosure indices constrain the generalizability of results. Overall, this study provides timely empirical evidence on ESG adoption within the unique Egyptian context and its influence on integrated reporting (IR). It contributes to literature by identifying specific BOD characteristics that enhance IRDQ. The results offer practical insights into how companies, regulators, and stakeholders can leverage board diversity and size as well as ESG disclosure to improve IRDQ.